Novel Calcium Oxide-Enhancement Phosphorus Recycling Technique through Sewage Sludge Pyrolysis - S. Tang; Yan, F.; Zheng, C.; Z. Zhang (ACS Sustainable Chemistry and Engineering, 2018)
Municipal sewage sludge is abundant and rich in phosphorus, making it a promising alternative phosphorus reserve. A good knowledge of the phosphorus transformation during pyrolysis will underlie the industrial phosphorus recycling and reclamation of sewage sludge. This work first advanced a novel calcium oxide (CaO)-enhancement phosphorus-recycling technique based on pyrolysis of sewage sludge, by regulating the transformation of phosphorus in sewage sludge during pyrolysis through the CaO addition. The obtained results indicated that CaO addition promoted the formation of hydroxylapatite, which is a desirable phosphorus species for plant growth. The factors of pyrolysis temperature and inherent composition of sewage sludge both influenced the fraction of hydroxylapatite during pyrolysis. An increase in pyrolysis temperature and a sludge with a high content of ash and a low content of volatile matters potentially promoted the transformation of P from organic phosphorus to the inorganic species during pyrolysis with the addition of CaO, particularly for the formation of hydroxylapatite. Increasing CaO addition significantly increased the fraction of hydroxylapatite in the obtained char, and the maximum content of 25 wt % hydroxylapatite over total phosphorus was attained. This enhanced transformation of hydroxylapatite may be potentially attributed to the interaction between CaO and the polyphosphate with the aid of the inherent minerals that appeared to benefit the immobilization of phosphorus during sludge pyrolysis. As the formation of hydroxylapatite was enhanced, this facile technology of CaO-enhancement sewage sludge pyrolysis could be used for the direct recycling of P as well as the disposal of sewage sludge. © Copyright 2018 American Chemical Society.
Keywords: Hydroxyapatite; Inorganic species; Lime; Municipal sewage sludge; Organic phosphorus; Phosphorus; Phosphorus species; Phosphorus transformations; Plant life extension; Pyrolysis; Pyrolysis temperature; Recycling; Recycling techniques; Sewage sludge; Sewage sludge pyrolysis; Sludge disposal